Vascular access - Concept Media, inc (Irvine, CA : Concept Media, 2008)
Scenarios are used throughout [this series] to illustrate nursing assessments and interventions associated with vascular access as well as techniques that can be used for patient-family education. Various types of catheters are used to improve patient outcomes. This series discuses several of the most common procedures.
130.1. Peripheral IVs (17 min.) -- 130.2. Peripherally inserted central catherters (22 min.) -- 130.3. Peripheral arterial lines (14 min.) -- 130.4. Central venous access (25 min.) -- 130.5. Central venous access blood draw and dressing change (10 min.)
Accompanying materials: Instructor's guides (130 CD-ROM) and Self-grading tests (130 CD-ROM)
Writer, Celeste Salsgiver; reviewers/consultants, Adrian Taves, Michele Grantham, Ann Leatherman
Narrator: Peggy Redd
DVD
No Masters.
Keywords: Medical instruments and apparatus; Infusions, intravenous -- Nursing; Phlebotomy -- Nursing; IV therapy